Characterizing the influence of different drying methods on chemical components of Panax notoginseng leaves by heart-cutting two-dimensional liquid chromatography coupled to orbitrap high-resolution mass spectrometry. (1st February 2022) - Ma, Li-Juan; Ma, Ni; Cao, Ji-Liang; Wan, Jian-Bo
Highlights: A heart-cutting 2D-LC-HRMS method was developed. Seventeen main saponins in PNL processed by different drying methods were quantified. Severe ginsenoside transformation occur in PNL by SUN and HAD50, but not SAD, HAD25 and SD. Only SD can inactivate the proteins that mediate ginsenoside transformation. Different drying methods greatly affect the quality of PNL products. Abstract: Panax notoginseng leaves (PNL) was considered as a promising functional food ingredient with abundant protopanaxdiol ginsenosides. In this study, the influence of different drying methods on chemical components in PNL was characterized by a newly developed heart-cutting 2D-LC-HRMS. Our data indicates that vigorous ginsenoside transformation occurs in PNL processed by sun-air drying and hot-air drying (HAD) at 50 °C, but not shade-air drying (SAD), HAD at 25 °C and steaming prior to drying (SD). Specifically, the main components of PNL, ginsenosides Rb3, Rc, Rb2, Rb1 and Rd, can be transformed into notoginsenosides Fd and Fe, ginsenoside Rd2, Gypenoside XVII and ginsenoside F2, respectively, by highly selective cleavage of β-1, 2-glucosidic linkage at the C-3 position. Only SD can inactivate the proteins that mediate this transformation. Different drying methods also greatly affect the quality of PNL products extracted by the conventional decoction method. These findings offer the scientific basis to design industrial drying methods for ensuring the quality of PNL.